MINAT INVESTASI GENERASI Z : PERAN LITERASI KEUANGAN, MEDIA SOSIAL DAN PENGARUH SOSIAL - Rimawan, Muhammad; Puji Muniarty; Alwi, Alwi; Hanifah Muthiah; Ovriyadin, Ovriyadin; Rosa Yuliati (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the influence of financial literacy, social media, and social influence on the investment interest of Generation Z. The research is motivated by the increasing number of young investors in Indonesia, which is not always accompanied by sufficient financial understanding. A quantitative approach was used, employing multiple linear regression analysis. The population consisted of active students at STIE Bima aged 18–26 years, selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using SPSS. The results show that financial literacy and social influence have a positive and significant effect on investment interest, while social media does not have a significant effect. Simultaneously, all three variables significantly affect Generation Z’s investment interest, with a coefficient of determination (R²) of 62.4%. These findings highlight the importance of financial education and social environment in shaping investment behavior among young people. This study contributes to the development of more effective and targeted investment education strategies for the digital-native generation.